African Brain Circulation: Beyond the Drain-Gain Debate - Patterson, Rubin (International Studies in Sociology and Social Anthropology, 2007)
Transnational society is a new field of study, just as brain circulation is a new development strategy for the global South. This book contributes to the growing scholarship on transnational society and brain circulation, thus highlighting the dynamic social practices already underway.